The role and application of internal and external load indicators in monitoring fatigue in rugby players - a narrative review - Lv, X.; Yang, J.; Suo, L.; Han, W. (Frontiers in Sports and Active Living, 2025)
Although the scientific understanding of training load and fatigue monitoring in rugby has advanced considerably, critical challenges remain in the systematic implementation and integrative interpretation of internal and external load metrics. Through a comprehensive narrative review of PubMed, Web of Science, and CNKI databases encompassing literature through December 2024, we critically examined the application and limitations of multiple monitoring approaches including GPS and inertial microsensor technologies, time-motion analysis, neuromuscular function assessments, subjective rating scales, cardiac autonomic markers, and biochemical profiling. Our synthesis reveals substantial methodological heterogeneity and lack of consensus regarding optimal implementation strategies for these metrics in rugby-specific contexts. Moving forward, research efforts should prioritize three key areas: (1) developing sport-specific algorithms for multi-modal data integration that account for rugby's unique physical demands; (2) establishing individualized monitoring protocols that consider positional requirements and athlete characteristics; and (3) validating predictive models that enhance the precision of load quantification while supporting evidence-based training prescription and injury risk mitigation in competitive rugby environments. These advancements would address current limitations in monitoring practice and provide practitioners with more reliable tools for optimizing athlete preparation and performance outcomes.